2004
DOI: 10.1002/ijc.20244
|View full text |Cite
|
Sign up to set email alerts
|

Against which human papillomavirus types shall we vaccinate and screen? the international perspective

Abstract: At least 15 types of HPV have been associated with cervical cancer, but current HPV vaccines confer only type-specific immunity. To determine geographic variations in the HPV type distribution in cervical cancer, we carried out a pooled analysis of data from an international survey of HPV types in cervical cancer and from a multicenter case-control study, both co-coordinated by the IARC. Study cases were 3,607 women with incident, histologically confirmed cervical cancer recruited in 25 countries. HPV DNA dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
678
10
47

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 964 publications
(774 citation statements)
references
References 27 publications
39
678
10
47
Order By: Relevance
“…Therefore, administration of a bivalent HPV-16/18 vaccine in this population before they get exposed might have the potential to prevent the majority of highgrade lesions in this population, but this would need to be determined in prospective studies. It is not known, however, whether successful control of HPV-16 or -18 might not lead to replacement by other oncogenic HPV types, which are highly prevalent in our population as in many parts of sub-Saharan Africa (Muñoz et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, administration of a bivalent HPV-16/18 vaccine in this population before they get exposed might have the potential to prevent the majority of highgrade lesions in this population, but this would need to be determined in prospective studies. It is not known, however, whether successful control of HPV-16 or -18 might not lead to replacement by other oncogenic HPV types, which are highly prevalent in our population as in many parts of sub-Saharan Africa (Muñoz et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…On the area of cervical cancer prevention, much emphasis and hope has lately been given on human papillomavirus (HPV) vaccines being tested around the world (Koutsky et al, 2002;Harper et al, 2004;Munoz et al, 2004). Nevertheless, organised population-based screening is still the most effective way to control for cervical cancer (The working group of IARC, 2005).…”
mentioning
confidence: 99%
“…Ongoing epidemiological studies have shown that infection of the genital tract with HPV is very common, with over 50% of sexually active young women and young men acquiring at least one genital HPV infection in the first 5 years of sexual activity [9]. Cervical cancer is causally associated with infection by one of a subset of about 15 genital HPV termed "high-risk" [10]. Worldwide, two of the high-risk HPV types, HPV16 and 18, are responsible for approximately 70% of cervical cancer and are also the HPV types most often found in HPV-associated cancers at other sites.…”
Section: Human Papillomaviruses (Hpv)mentioning
confidence: 99%